Design Of E-Wallet And Loyalty Application Using Aes Model On Coffee Terminal - Hafiza Siraj Abshar; Heri Wahyudi; Asep Sudrajat; Muhammad Syukri (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This research seeks to tackle the issues of transaction efficiency, payment convenience, transaction security, and minimal consumer involvement encountered by